Case Report: Surgical management of idiopathic pulmonary aneurysms and review surgical approaches - Wu, Kui; Fan, Xuan; Hu, Xuanyi; Li, Xuejun; Yang, Siyuan (Frontiers in Cardiovascular Medicine, 2023)
Idiopathic pulmonary aneurysm is a clinically rare condition characterized by an unknown etiology and episodic occurrence. Despite its rarity, idiopathic pulmonary artery aneurysm poses potential risks to patients. Currently, there is a lack of established clinical guidelines and consensus regarding its management, leading to ongoing controversies in treatment strategies. Particularly, the optimal approach for addressing the main pulmonary artery, its branches, and the pulmonary artery valve remains uncertain. A 57-year-old female patient presented with chest pain and tightness, leading to the diagnosis of idiopathic pulmonary artery aneurysm after excluding other potential causes. Subsequently, she underwent surgical treatment. However, during the surgery, the pulmonary artery wall was found to be extremely weak, prompting us to employ a surgical approach involving the utilization of autologous vessel wrapping with artificial grafts. By summarizing almost all surgical treatment strategies reported in recent years, including the management of pulmonary artery vessels and the pulmonary valve, we have developed a treatment flow chart. This flowchart serves as a valuable guide for the management of future cases presenting similar challenges, offering clinicians valuable insights and evidence-based recommendations.